Factors Influencing malnutrition in children five years and below in Serian District in Sarawak - Eunice Melissa, Joseph (Universiti Malaysia Sarawak (UNIMAS), 2012)
Malaysia has been proressing well in both socioeconomics status and health care services; however , malnutrition is still prevalent in rural areas among the poor households. The aetiology of childhood malnutrition is complex involving interactions of multiple factors at individual, family and community levels. This study aimed to determine the prevalance of malnutrition and factors influencing malnutrition among children aged five years and below in serian district in Sarawak. It was a cross sectional study. The children's weights and heights/lengths were measured. Socio-demographic information, factors influencing malnutrition, 24-hour diet recall and food security was gathered through a structured interview with the mothers/caretakers of the children.